Adding dried distillers grains to swine diets affects feed preference - C W Hastad; Jim L Nelssen; Robert D Goodband; Michael D Tokach; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
Three studies were conducted to evaluate the effects of dried distillers grains with solubles (DDGS) on feed intake in growing pigs. In all experiments, pigs were housed in 10.5 × 10.3 ft pens with four 1-hole feeders in each pen to allow pigs to choose from four dietary treatments. In Experiment 1, we evaluated the influence of DDGS drying method on palatability of DDGS. Diets were a control corn soybean-meal diet or a corn soybean-meal diet with 30% DDGS from one of two drying techniques (plant dried, hand dried, or not dried). Overall, ADFI was less (P0.55) on feed intake. These studies illustrate that pigs prefer corn-soybean diets to diets containing DDGS. The decrease in palatability seems to increase with increasing amounts of dried distiller grains. Although the nutrient content of DDGS make it an attractive ingredient for swine diets, palatability problems may affect pig performance, even when DDGS is included at low rates in the diet.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Swine; Pigs; Feed intake; DDGS